2018
DOI: 10.1080/09168451.2018.1429886
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a combination of inulin and polyphenol-containing adzuki bean extract on intestinal fermentation in vitro and in vivo

Abstract: The effect of a combination of inulin (INU) and polyphenol-containing adzuki bean extract (AE) on intestinal fermentation was examined in vitro using fermenters for 48 h and in vivo using rats for 28 d. The total short-chain fatty acid concentrations in the fermenters were decreased by a combination of INU and AE, but the concentration in the INU + AE group was higher than the cellulose (CEL) and CEL + AE groups. The cecal propionate concentration was increased by a combination of INU and AE compared with thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…After a 7 d acclimation period, the rats were randomly assigned to four groups and fed one of the experimental diets (Oriental Yeast Co., Ltd., Tokyo, Japan) formulated based on the AIN-93G diet (Table 1) for 4 wk. Care and dissection of the rats were conducted as previously described (17).…”
Section: Methodsmentioning
confidence: 99%
“…After a 7 d acclimation period, the rats were randomly assigned to four groups and fed one of the experimental diets (Oriental Yeast Co., Ltd., Tokyo, Japan) formulated based on the AIN-93G diet (Table 1) for 4 wk. Care and dissection of the rats were conducted as previously described (17).…”
Section: Methodsmentioning
confidence: 99%
“…Ammonia-nitrogen (AN), Immunoglobulin A (IgA) in cecal digesta and serum (fasting) biochemical analysis. AN and IgA in the diluted samples of cecal content and the serum biochemical parameters were analyzed according to the procedures reported in (6).…”
Section: Methodsmentioning
confidence: 99%
“…Butyrate is a major fuel source for ileal and colonic enterocytes (14,15). Rodent and clinical studies have shown metabolic improvements after supplementation with fibers and/or polyphenols (13,(16)(17)(18)(19) or pure SCFAs (20)(21)(22). Counterintuitively, higher SCFA Abbreviations: EE, Energy expenditure; GP, grape polyphenol; HFD, high fat diet; HFHS, high fat high sucrose; LFD, low fat diet; NAFLD, non-alcoholic fatty liver disease; OGT(T), oral glucose tolerance (test); PAC, proanthocyanidin; SCFA, short chain fatty acid; WD, Western diet; WD-GP, Western diet with grape polyphenols.…”
Section: Introductionmentioning
confidence: 99%